1998
DOI: 10.1046/j.1365-2796.1998.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

A UK Consensus Group on management of glucocorticoid‐induced osteoporosis: an update

Abstract: . Eastell R, Reid DM, Compston J, Cooper C, Fogelman I, Francis RM, Hosking DJ, Purdie DW, Ralston SH, Reeve J, Russell RGG, Stevenson JC, Torgerson DJ (University of Sheffield Medical School, Sheffield; University of Aberdeen, Aberdeen; University of Cambridge School of Clinical Medicine, Addenbrooke's Hospital, Cambridge; Southampton General Hospital, Southampton; Guy's Hospital, London; Freeman Hospital, Newcastle upon Tyne; Nottingham City Hospital, Nottingham; Hull Royal Infirmary, Hull; Wynn Institute fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
0
21

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(188 citation statements)
references
References 124 publications
7
159
0
21
Order By: Relevance
“…An exercise program should also be initiated, although this may be limited by restrictions from the underlying illness. Other published guidelines largely agree with the recommendations above, except for some minor differences 4142…”
Section: Specific Types Of Osteoporosissupporting
confidence: 58%
“…An exercise program should also be initiated, although this may be limited by restrictions from the underlying illness. Other published guidelines largely agree with the recommendations above, except for some minor differences 4142…”
Section: Specific Types Of Osteoporosissupporting
confidence: 58%
“…A diagnostic work-up, followed by therapeutic intervention, is advised for patients using oral corticosteroids at doses of 15 mg day x1 or more and those using doses between 7.5 and 15 mg day x1 and with strong risk factors for fracture. All other patients with doses of 7.5 mg or more should, according to these guidelines, be monitored periodically using bone-mass measurements [8]. These guidelines, based on a review of literature, were developed to provide a more systematic approach to the identi®cation of highrisk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for the ef®cacy of these therapies has been summarized by Eastell [8]. Bisphosphonates have been most widely studied in patients with corticosteroid-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the numbers per se, it is obvious that existing guidelines on the prevention and treatment of glucocorticoid-induced osteoporosis (34,(37)(38)(39) are only incompletely followed. In a recently published article, Solomon et al (40) reported that the practical implementation of such guidelines is not very consistent.…”
mentioning
confidence: 99%